India’s Roadmap of Convergence to International Financial Reporting Standards (IFRS) - Gupta, Ram Kesh; Kumar, D. N. S.; Gupta, Deepika Ravindrakumar (Indian Journal of Finance, 2012)
International Financial Reporting Standards (IFRS) previously known as International Accounting Standards (IAS) are standards and interpretations adopted by the International Accounting Standards Board (IASB). IASB adopted IAS in April 2001, and renamed it as IFRS. IFRS are 'principle-based' standards rather than 'rule-based' standards that are currently followed. Under IFRS, there is a need to apply professional judgments that are consistent with intent and spirit of standards. The Indian companies have to shape up their models and strategies in order to comply with the IFRS roadmap. This research paper attempts to highlight challenges; steps needed to be taken to address such challenges and map the current preparation for convergence to IFRS. India will enjoy numerous benefits by joining the ranks of a 100-plus group of nations that have successfully implemented IFRS like the European Union, Australia, Singapore, Sri Lanka and others.